Oviposition and larval development of a stem borer, Eoreuma loftini, on rice and non‐crop grass hosts. Issue 3 (5th February 2013) - Beuzelin, J.M.; Wilson, L.T.; Showler, A.T.; Mészáros, A.; Wilson, B.E.; Way, M.O.; Reagan, T.E.
Abstract A greenhouse study compared oviposition preference and larval development duration of a stem borer, Eoreuma loftini (Dyar) (Lepidoptera: Crambidae), on rice, Oryza sativa L. cv Cocodrie (Poaceae), and four primary non‐crop hosts of Texas Gulf Coast rice agroecosystems. Rice and two perennials, johnsongrass, Sorghum halepense (L.) Pers., and vaseygrass, Paspalum urvillei Steud. (both Poaceae), were assessed at three phenological stages. Two spring annuals, brome, Bromus spec., and ryegrass, Lolium spec. (both Poaceae), were assessed at two phenological stages. Phenological stages represented the diversity of plant development stages E. loftini may encounter. Plant fresh biomass, dry biomass, and sum of tiller heights were used as measures of plant availability. Accounting for plant availability, rice was preferred over non‐crop hosts, and intermediate and older plants were preferred over young plants. Johnsongrass and vaseygrass were 32–60% as preferred as rice when considering the most preferred phenological stages of each host. Brome and ryegrass received few or no eggs, respectively. Eoreuma loftini larval development (in degree days above developmental threshold temperatures) was fastest on rice and slowest on johnsongrass and vaseygrass. Development duration was only retarded by plant stage on young rice plants. Foliar and stem free amino acid concentrations were determined to help provide insights on the mechanisms of E. loftini oviposition preference and developmental performance.